Bioimaging marine crustacean brain: quantitative comparison of micro-CT preparations in an Alpheid snapping shrimp - Chapuis, Lucille; Andres, Cara-Sophia; Gerneke, Dane A.; Radford, Craig A. (Frontiers in Neuroscience, 2024)
Non-invasive bioimaging techniques like X-ray micro-computed tomography (μCT), combined with contrast-enhancing techniques, allow the 3D visualization of the central nervous system in situ, without the destruction of the sample. However, quantitative comparisons of the most common fixation and contrast-enhancing protocols are rare, especially in marine invertebrates. Using the snapping shrimp (Alpheus richardsoni) as a model, we test three common fixation and staining agents combinations to prepare specimens prior to μCT scanning. The contrast ratios of the resulting images are then quantitatively compared. Our results show that a buffered iodine solution on a specimen fixed with 10% formalin offers the best nervous tissue discriminability. This optimal combination allows a semi-automated segmentation of the central nervous system organs from the μCT images. We thus provide general guidance for μCT applications, particularly suitable for marine crustaceans. Species-specific morphological adaptations can then be characterized and studied in the context of evolution and behavioral ecology.